Pneumonia is the Leading Cause of Death from Respiratory Diseases at High Altitude In La Paz, Bolivia - Marcelino, Gonzales; Navia, Casto; Tamayo , Carlos; Villarroel , Martin; Bairam , Aida; Sanchez , Lida; Arias-Reyes , Christian; Soliz, Jorge (International Journal of Innovative Research in Medical Science, 2024)
Chronic obstructive pulmonary disease (COPD) and asthma are major contributors to mortality resulting from respiratory diseases among sea-level populations. In high altitude environments, located between 2500 and 3600 meters, where oxygen availability decreases (hypoxia), pulmonary edema has been identified as the main cause of mortality among transient visitors to such high regions. However, despite the existence of physiological adaptations among permanent residents of high altitudes (characterized by increased ventilation, increased red blood cell counts, vasodilation, and an increased muscle contraction pump), extensive research on fatal respiratory diseases that prevalence in this demographic remains low. In this research effort, we analyzed 1,214 mortality records from 2017 in La Paz, Bolivia (located at 3,600 meters). Our results indicate that pneumonia is the leading cause of death in these high-altitude Bolivian cities. This is in stark contrast to pneumonia's position as the fourth leading cause of death at sea level, accentuating the distinctive health challenges faced by populations residing at high altitudes.